(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article discusses the issues of raising the status of women, increasing their activity in state and society management, education, health care, science and other fields, and increasing their legal literacy. In addition, it will be discussed about the work being done to ensure their equality in socio-cultural, political and gender issues.